2016
DOI: 10.1177/1368430215612225
|View full text |Cite
|
Sign up to set email alerts
|

Imagined contact encourages prosocial behavior towards outgroup members

Abstract: According to the intergroup contact hypothesis (Allport, 1954), we can reduce prejudice between different cultural groups by encouraging interaction between them. Volumes of evidence have now supported this hypothesis. Pettigrew and Tropp's (2006) meta-analysis of 515 studies confirms the robust, negative relationship between contact and prejudice. This effect is strengthened by certain "optimal" conditions (e.g., equal status of the groups in the situation, intergroup cooperation, common goals, and authority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 79 publications
4
35
0
1
Order By: Relevance
“…Research has provided evidence for several mediators of the effects of imagined contact, which largely overlap with those identified for direct contact. In particular, there is evidence that the effects of imagined contact are mediated by outgroup attitudes (Birtel & Crisp, 2012b, Study 3;Harwood et al, 2011;Husnu & Crisp, 2010a;West, Hotchin, & Wood, 2017), infrahumanization (Prati & Loughnan, 2018), outgroup trust (Hodson, Dube, & Choma, 2015;Meleady & Seger, 2016;Pagotto, Visintin, De Iorio, & Voci, 2013;, intergroup anxiety (Birtel & Crisp, 2012b;Ioannou, Hewstone, & Al Ramiah, 2016;Stathi Tsantila, et al, 2012;West & Greenland, 2016;West, Holmes, & Hewstone, 2011) and perspective-taking (Husnu & Crisp, 2015). Outgroup attitudes (Stathi et al, 2014), outgroup trust and self-disclosure have been shown to mediate the imagined contact effect in children.…”
Section: Mediating Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has provided evidence for several mediators of the effects of imagined contact, which largely overlap with those identified for direct contact. In particular, there is evidence that the effects of imagined contact are mediated by outgroup attitudes (Birtel & Crisp, 2012b, Study 3;Harwood et al, 2011;Husnu & Crisp, 2010a;West, Hotchin, & Wood, 2017), infrahumanization (Prati & Loughnan, 2018), outgroup trust (Hodson, Dube, & Choma, 2015;Meleady & Seger, 2016;Pagotto, Visintin, De Iorio, & Voci, 2013;, intergroup anxiety (Birtel & Crisp, 2012b;Ioannou, Hewstone, & Al Ramiah, 2016;Stathi Tsantila, et al, 2012;West & Greenland, 2016;West, Holmes, & Hewstone, 2011) and perspective-taking (Husnu & Crisp, 2015). Outgroup attitudes (Stathi et al, 2014), outgroup trust and self-disclosure have been shown to mediate the imagined contact effect in children.…”
Section: Mediating Processesmentioning
confidence: 99%
“…Husnu & Crisp, 2010a, 2010bStathi, Cameron, Hartley, & Bradford, 2014;R. N. Turner, West, & Christie, 2013), helping intentions , and behavior (e.g., Birtel & Crisp, 2012a;Meleady & Seger, 2016;.…”
mentioning
confidence: 99%
“…Finseraas et al 2019), and much of this work relies on self-reports of previous contact experiences and attitudes or mentally simulating positive contact (e.g. Meleady and Seger 2017).…”
Section: The Current Researchmentioning
confidence: 99%
“…Since Turner et al () first demonstrated that imagined contact could reduce prejudice, a growing body of subsequent research has also found support for the “imagined contact hypothesis” (Crisp & Turner, , p. 125; see Miles & Crisp, for a meta analysis), showing that imagined contact can reduce intergroup anxiety (Turner et al, ; West, Holmes, & Hewstone, ), improve intergroup attitudes (Turner & Crisp, ), reduce implicit prejudice as well as explicit prejudice (Turner & Crisp, ), and alter subsequent behavior (Meleady & Seger, ; Turner & West, ; West, Turner, & Levita, 2015).…”
Section: Introductionmentioning
confidence: 99%